Quantum Transport by Spin‐Polarized Edge States in Graphene Nanoribbons in the Quantum Spin Hall and Quantum Anomalous Hall Regimes. Issue 11 (15th July 2018) - Pournaghavi, Nezhat; Holmqvist, Cecilia; Pertsova, Anna; Canali, Carlo M.
Abstract : Using the non‐equilibrium Green's function method and the Keldysh formalism, we study the effects of spin–orbit interactions and time‐reversal symmetry breaking exchange fields on non‐equilibrium quantum transport in graphene armchair nanoribbons. We identify signatures of the quantum spin Hall (QSH) and the quantum anomalous Hall (QAH) phases in non‐equilibrium edge transport by calculating the spin‐resolved real space charge density and local currents at the nanoribbon edges. We find that the QSH phase, which is realized in a system with intrinsic spin–orbit coupling, is characterized by chiral counter‐propagating local spin currents summing up to a net charge flow with opposite spin polarization at the edges. In the QAH phase, emerging in the presence of Rashba spin–orbit coupling and a ferromagnetic exchange field, two chiral edge channels with opposite spins propagate in the same direction at each edge, generating an unpolarized charge current and a quantized Hall conductance G = 2 e 2 / h . Increasing the intrinsic spin–orbit coupling causes a transition from the QAH to the QSH phase, evinced by characteristic changes in the non‐equilibrium edge transport. In contrast, an antiferromagnetic exchange field can coexist with a QSH phase, but can never induce a QAH phase due to a symmetry that combines time‐reversal and sublattice translational symmetry. Abstract : The effects of spin–orbit interactions and time‐reversal symmetry breaking exchange fields on non‐equilibrium quantum transport in graphene armchair nanoribbons are studied using the non‐equilibrium Green's function method and the Keldysh formalism. Signatures of the quantum spin Hall and the quantum anomalous Hall phases are identified through calculations of the spin‐resolved real space charge density and local currents at the nanoribbon edges.